Chitin and chitosan materials from black soldier fly (Hermetia illucens): An insight onto their thermal degradation and mechanical behavior linked to their copolymeric structure - Maria-Beatrice Coltelli; Vito Gigante; Luca Panariello; Laura Aliotta; Carmen Scieuzo; Patrizia Falabella; Andrea Lazzeri (Polymer Testing)
Chitin and chitosan from black soldier fly (Hermetia illucens) rearing, associated with the different development stages (larvae, pupal exuviae and adults), were characterized by ATR-IR determining the RAC ratio, associated with the acetylation degree of the polymers. It was possible to compare the different samples, and it was detected that the chitin from adult insects was the one with the highest acetylation degree. Discoloured chitin samples were also tested, and they showed a lower acetylation degree than the not discoloured ones. Chitosan samples, obtained by heterogeneous deacetylation, from larvae and pupal exuviae were the most deacetylated and they resulted similar to commercial chitosan from shrimps. The characterization of samples by thermogravimetry in nitrogen was carried out and their thermal behaviour resulted different for chitin and chitosan samples. For chitosan samples an additional mass loss at lower temperature could be revealed with respect to chitin, and its quantitative value decreased by increasing the RAC ratio. It could be deduced that the chitosan samples from Hermetia illucens (HI) were mainly blocky, except for the chitosan sample obtained from larvae and the commercial chitosan from shrimp. For the latter samples a mainly homogeneous distribution of acetamide groups on the polymer backbone could be hypothesized. The mechanical properties of films obtained by solvent casting of acidic water solutions of chitosan samples were measured. The highest values for tensile strength and elongation at break were observed for the film obtained by chitin from H. illucens larvae or from commercial chitosan from shrimps. Interestingly, these chitosan samples are those corresponding to a homogenous distribution of acetyl groups, suggesting that this feature can play a significant role in influencing the mechanical properties of chitosan films.